Nobiletin Attenuates Pathological Cardiac Remodeling after Myocardial Infarction via Activating PPARγ and PGC1α. (11th August 2021) - Zhou, Yufei; Yin, Ting; Shi, Mengsha; Chen, Mengli; Wu, Xiaodong; Wang, Kai; Cheang, Iokfai; Li, Yanxiu; Shang, Hongcai; Zhang, Haifeng; Li, Xinli
Abstract : Rationale . Pathological cardiac remodeling serves as a vital mechanism during the progression from myocardial infarction (MI) to chronic heart failure (CHF). Nobiletin (NOB), an active monomer extracted from the peel of citrus fruit, has been reported to have beneficial effects in cardiovascular diseases. Our study was aimed at describing the specific mechanisms through which NOB protects against pathological cardiac remodeling after MI. Materials and Methods . C57BL/6 mice were treated with coronary artery ligation to generate an MI model, followed by treatment for 3 weeks with NOB (50 mg/kg/d) or vehicle (50 mg/kg/d), with or without the peroxisome proliferator-activated receptor gamma (PPAR γ ) inhibitor T0070907 (1 mg/kg/d). Cardiac function (echocardiography, survival rate, Evans blue, and triphenyl tetrazolium chloride staining), fibrosis (Masson's trichrome staining, quantitative real-time polymerase chain reaction (qRT-PCR), and western blot (WB)), hypertrophy (haematoxylin-eosin staining, wheat germ agglutinin staining, and qRT-PCR), and apoptosis (WB and terminal deoxynucleotidyl transferase dUTP nick-end labelling (TUNEL) staining) were evaluated. Hypoxia-induced apoptosis (TUNEL, WB) and phenylephrine- (PE-) induced pathological hypertrophy (immunofluorescence staining, qRT-PCR) models were established in primary neonatal rat ventricular myocytes (NRVMs). The effects of NOB with or without T0070907 were examined for the expression of PPAR γ and PPAR γ coactivator 1 α (PGC1 α ) by WB in mice and NRVMs. The potential downstream effectors of PPAR γ were further analyzed by WB in mice. Results . Following MI in mice, NOB intervention enhanced cardiac function across three predominant dimensions of pathological cardiac remodeling, which reflected in decreasing cardiac fibrosis, apoptosis, and hypertrophy decompensation. NOB intervention also alleviated apoptosis and hypertrophy in NRVMs. NOB intervention upregulated PPAR γ and PGC1 α in vivo and in vitro . Furthermore, the PPAR γ inhibitor abolished the protective effects of NOB against pathological cardiac remodeling during the progression from MI to CHF. The potential downstream effectors of PPAR γ were nuclear factor erythroid 2-related factor 2 (Nrf-2) and heme oxygenase 1 (HO-1). Conclusions . Our findings suggested that NOB alleviates pathological cardiac remodeling after MI via PPAR γ and PGC1 α upregulation.